PELATIHAN PEMBUATAN MEDIA INTERAKTIF BERBASIS MODEL PROJECT BASED LEARNING PENDIDIK DI SEKOLAH DASAR - Susandi, Ari; Zativalen, Oriza; Kharisma, Ahmad Ipmawan; Irmaningrum, Rizka Novi; Huda, Mochammad Miftachul; Amelia, Delora Jantung; Istiq’faroh, Nurul (Jurnal Edukasi Pengabdian Masyarakat, 2026)
The community service program that we carried out aims to train the creativity of elementary school educators in the Babat Lamongan elementary and secondary education environment through the creation of interactive media. The methods used are the planning stage, the implementation stage and the evaluation stage. Based on the results of the activity, it shows that all educators can follow and create interactive media based on the project-based learning model in community service activities with full creativity and enthusiasm. Interactive media based on project-based learning can be one of the media for educators to tell and explain their ideas in the learning process in elementary schools according to child development. Through this interactive media, students can develop writing and speaking skills through interactive media. The success and creativity of educators in the Babat Lamongan elementary and secondary education environment in creating unique and interactive interactive media as a whole, this activity can be a valuable media to support the writing and speaking skills of students at the elementary school level to the maximum.